Spasialisasi Dan Praktik Konglomerasi Media Kelompok Kompas Gramedia - Rahmawati Zulfiningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This study aims to determine the spatialization and practices of media conglomeration by Kompas Gramedia group. This type of research is descriptive qualitative. In this research, data collection techniques used in-depth interviews, library research, and documentation. This study uses a technique Interactive Analysis Model Miles and Huberman. Spatialization as a process for overcoming space and time, map out the extent to which the media were able to present their products to the front of the reader, viewer, or consumers with the limits of space and time. The results indicate that the practice of spatialization conducted by Kompas Gramedia Group is to follow the model of industrial economy. It is characterized by the abundance of media and accelerate the results to get a low cost for the production or efficiency. This indicates the growth spirit of capitalism in the media industry. The media industry, which was built in the spirit of capitalism would produce media messages or product oriented capital increase. The conglomeration of media make the media do their efficiency is reflected in the value chain of media products. As the result, media also could not avoid about the content that will be the same. With equalizer for the content of these media, people in the audience do not have the freedom to select appropriate media content as what they want.